Marrow versus peripheral blood for geno-identical allogeneic stem cell transplantation in acute myelocytic leukemia: Influence of dose and stem cell source shows better outcome with rich marrow - (:unkn) unknown (American Society of Hematology, 2003)
Several studies have compared bone marrow (BM) and peripheral blood (PB) as stem cell sources in patients receiving allografts, but the cell doses infused have not been considered, especially for BM. Using the ALWP/EBMT registry, we retrospectively studied 881 adult patients with acute myelocytic leukemia (AML), who received a non-T-depleted allogeneic BM (n = 515) or mobilized PB (n = 366) standard transplant, in first remission (CR1), from an HLA-identical sibling, over a 5-year period from January 1994. The BM cell dose ranged from 0.17 to 29 × 108/kg with a median of 2.7 × 108/kg. The PB cell dose ranged from 0.02 to 77 × 10 8/kg with a median of 9.3 × 108/kg. The median dose for patients receiving BM (2.7 × 108/kg) gave the greatest discrimination. In multivariate analyses, high-dose BM compared to PB was associated with lower transplant-related mortality (RR = 0.61; 95% CI, 0.39-0.98; P = .04), better leukemia-free survival (RR = 0.65; 95% CI, 0.46-0.91; P = .013), and better overall survival (RR = 0.64; 95% CI, 0.44-0. 92; P = .016). The present study in patients with AML receiving allografts in first remission indicates a better outcome with BM as compared to PB, when the dose of BM infused is rich. © 2003 by The American Society of Hematology.